2012
DOI: 10.1080/00028487.2012.717517
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Related Changes in Habitat Quality and Use by Bonneville Cutthroat Trout in Regulated and Unregulated River Segments

Abstract: The availability of suitable habitat is often viewed as one of most important limiting factors for animal populations. In this study, we examined the composition and spatial distribution of stream habitat based on summer water temperature using airborne thermal imagery, floating temperature surveys, and fixed temperature data loggers in a regulated and unregulated segment of the Bear River in Idaho and Wyoming. We also used temperature‐sensitive radio telemetry tags to measure water temperature in habitats use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 50 publications
(76 reference statements)
1
27
0
Order By: Relevance
“…). Low densities of individuals may persist near warm boundaries if cold microrefugia are available (Hillyard and Keeley ), but refugia will become increasingly isolated in future years as the surrounding matrix of warmer waters continues to grow. Range contractions may also be exacerbated by upstream dispersal of predator species with warmer thermal preferences, as is occurring in some northwestern rivers with the expansion of Smallmouth Bass Micropterus dolomieu populations (Lawrence et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Low densities of individuals may persist near warm boundaries if cold microrefugia are available (Hillyard and Keeley ), but refugia will become increasingly isolated in future years as the surrounding matrix of warmer waters continues to grow. Range contractions may also be exacerbated by upstream dispersal of predator species with warmer thermal preferences, as is occurring in some northwestern rivers with the expansion of Smallmouth Bass Micropterus dolomieu populations (Lawrence et al.…”
Section: Discussionmentioning
confidence: 99%
“…We could not test the role of different habitat features, in particular that of thermal refugia. However, the diversity, abundance and connectivity of these habitat features are often reduced in agricultural streams due to water abstraction, riparian deforestation, channelization and deposited fine sediment (Allan, ; Hillyard & Keeley, ; Lange et al., ; Schinegger et al., ), thereby constraining behavioural responses.…”
Section: Discussionmentioning
confidence: 99%
“…This minimizes the potential role of prey density in the between‐river movement differences observed in the present study. For salmonids species, Hillyard and Keeley () found that the total distance (m) moved per week by Bonneville cutthroat trout ( Oncorhynchus clarki utah ) during the summer in a regulated river (average of 701 m; sedentary) was 11‐fold smaller than in an unregulated river (average of 7964 m; mobile); a movement pattern also observed in the Mississagi and Aubinadong rivers. Hillyard and Keeley () attributed the difference in mobility to small, infrequent, and widely distributed hospitable patches of cold water during warm summer months in the regulated river.…”
Section: Discussionmentioning
confidence: 99%
“…For salmonids species, Hillyard and Keeley () found that the total distance (m) moved per week by Bonneville cutthroat trout ( Oncorhynchus clarki utah ) during the summer in a regulated river (average of 701 m; sedentary) was 11‐fold smaller than in an unregulated river (average of 7964 m; mobile); a movement pattern also observed in the Mississagi and Aubinadong rivers. Hillyard and Keeley () attributed the difference in mobility to small, infrequent, and widely distributed hospitable patches of cold water during warm summer months in the regulated river. Water temperatures exceeded the upper thermal limit of the Bonneville cutthroat trout (24.2 °C; Johnstone and Rahel, ) in the study by Hillyard and Keeley ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation